An Analysis regarding Teachers' Continuous Training Needs in Romania between 2022 and 2024 - Tita, Dumitrel-Victor; Bold, Nicolae; Popa, Doinița; Matei, Mirela-Georgiana; Trusca, Claudia-Ionela (Didactica Danubiensis, 2024)
Teacher training has a great significance related to the quality of the educational system. The training process plays an important role in the continuous development of the teachers competencies in a context that has a permanent state of change under the social and human influences. This paper presents an analysis related to the teachers continuous training needs in Romania between 2022 and 2024, based on the development of a statistical instrument consisting in a survey addressed to the teachers who participated on training courses. The analysis was made based on two approaches. The first one is the statistical approach, in which direct observations based on quantitative and qualitative data from the responses was made. The second one is related to an analysis of specific needs that were determined to be the most influential in the first part of the analysis. The second part was made using machine-learning (ML)-based instruments, such as Natural Language Processing (NLP) or clustering based on the open responses and multiple-choice items. The research showed that a great deal of importance regarding training needs is related to the development of good practices and the integration of new technologies within the educational process.